Beneficial and harmful intestinal microbiota in poultry farming: Review (Research, Society and Development, 2020)
Currently, dysbiosis, rupture of the intestinal barrier and inflammation have become concerns of industrial poultry, since they culminate in the physiological and productive impairment of birds. The objective was to discuss the role of the intestinal microbiota of birds in animal development, as well as to highlight the benefits and/or losses caused by these microorganisms. The methodology adopted was a descriptive study, with a bibliographic review of scientific papers published in different indexed bases, with a time frame of the last decades. It was found that the use of sequencing the RNA ribosomal gene (rRNA) 16S is an important tool to identify and enumerate the intestinal bacteria present in production birds. Regarding the composition of the microbiota, in the small intestine there are mainly Lactobacillus, Streptococcus, Enterococcus, Bifidobacterium, Bacterioides, Clostridium, Fusobacterium and coliforms. In the large intestine, Lactobacillus, Bacterioides, Proteobacteria, Bacillus, Clostridium and Bifidobacterium. In the small intestine, bacteria participate in metabolism by improving nutrient absorption, hydrolyze polysaccharides to produce short-chain fatty acids, which will be absorbed and participate in important metabolic pathways in the supply of carbon and energy sources to birds. Despite the benefits of the microbiota in promoting a stable intestinal environment, in unfavorable situations, such as inadequate breeding, it can act as pathogens, produce toxic metabolites and impair the productive performance of birds.